ULAYAT RIGHT OF CUSTOMARY LAW COMMUNITY - Laturette, Adonia Ivonne (Pattimura Law Journal, 2017)
Ulayat right is a right that is given a magical aspect as a threatening force and can sanction as a basis of legitimacy of control over a territory or a plot of land called ulayat land. Ulayat Land is a plot of land that belongs to a group of people in a region. Although the customary law community has full customary authority to control, cultivate and utilize its ulayat land, but its formal juridical authority is not as strong as that of the State. The position of indigenous and tribal peoples is ultimately acknowledged conditional through various state regulations issued by the Government as in the Basic Agrarian Law Number 5 of 1960 Article 3. The conditional recognition that indigenous and tribal peoples can be recognized throughout 1) in reality Still exist, 2) in harmony with the times, 3) in accordance with national interests, 4) confirmed by local regulations. Such conditional recognition directly or has strengthened the State's domination of the rights possessed by society, it means that indigenous and tribal peoples will always be defeated when faced with state to defend their rights. The consequences of such an imbalance will clearly affect the role of indigenous and tribal peoples in the management and utilization of their ulayat land.